Woolfian border poetics and contemporary circadian novels - Ryall, Anka (Nordlit, 2014)
Virginia Woolf’s circadian novel Mrs Dalloway (1925) has inspired many successors, some of them important works in their own right. Although few of these novels are as explicitly linked to Mrs Dalloway as Michael Cunningham’s The Hours (1998), more recent novels such as Ian McEwan’s Saturday (2005) and Gail Jones’ Five Bells (2011) clearly pay homage to Woolf’s use of the one-day format to reveal whole lives and show how those individual private lives are entangled in history. The essay highlights one particular aspect of these three works, their imaginative and often transformative reworking of elements of Woolfian border poetics, particularly the predominance in Mrs Dalloway of boundary tropes – windows, doors, thresholds – that create a sense of synchronicity between present and past. Adapting Woolf’s boundary tropes to representations of contemporary realities, all three novels in different ways suggest how the present is deepened ”when backed by the past”, as Woolf puts it her memoirs; that is, when the present is not only informed by a remembered past but experienced in terms of both re-enactment and renewal, continuity and change.